NK cells in viral immunity - Lanier, Lewis (Henry Stewart Talks, 2021)
NK cell importance in viral immunity, Protection against cytomegalovirus in mice and humans, Receptor systems to counter cytomegalovirus infection, Killer cell immunoglobulin-like receptors, Different NK cell responses